Physiological profiling and energy system contributions during simulated epée matches in elite fencers - Yang, W.; Park, J.; Shin, Y.; Kim, J. (International Journal of Sports Physiology and Performance, 2022)
Purpose: The aim of this study was to investigate physiological responses and energetic contributions during simulated epée matches in elite fencers. Methods: Ten elite male fencers participated in simulated epée (direct elimination) matches. Simulated epée matches included 3 bouts of 3 minutes each with 1-minute rests between bouts. During these sessions, physiological variables such as mean and peak heart rate, peak and mean oxygen uptake (VO2peak and VO2mean), metabolic equivalents of task in VO2peak and VO2mean, and blood lactate concentrations (peak lactate concentration and delta blood lactate concentration) were measured. Furthermore, energetic contributions (oxidative [WOxi], glycolytic, and phosphagen) and time-motion variables were estimated. Results: Values of peak heart rate, mean heart rate, and WOxi (in percentages) were significantly higher in the second and third bouts compared with the first. VO2peak and metabolic equivalents of task in VO2peak were significantly higher in the first bout compared with the third bout. Values of delta blood lactate concentration and glycolytic contribution (in kilojoules and percentages) were significantly lower in the second and third bouts compared with the first. VO2mean and metabolic equivalents of task in VO2mean were significantly higher in the second bout compared with the third bout. Furthermore, WOxi (in kilojoules and percentage) was significantly higher in all bouts compared with phosphagen and glycolytic contributions. Low positive and negative correlations were seen between WOxi, VO2mean, sum of attacks and defense times, and the sum of time without attacks and defenses. Conclusions: Direct-elimination epée matches consist of high-intensity intermittent exercise, and the oxidative contribution is 80% to 90%. Improving aerobic conditioning may support high-intensity intermittent actions during entire epée matches in elite fencers.